2010
DOI: 10.1002/er.1673
|View full text |Cite
|
Sign up to set email alerts
|

Improving energy efficiency with the various control sequences for a VAV system through continuous commissioning®

Abstract: SUMMARYThis paper discusses the implementation of the innovative technologies for variable-air-volume (VAV) systems in a Continuous Commissioning (CC s ). The implemented building is a 5-story office facility with a total floor area of 8472 square meters, most of which is open space. An energy audit was conducted to evaluate the building's energy performance and identify potential cost-effective energy saving opportunities. Specific CC s measures were implemented in the building. This paper presents procedures… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…; Runming and Short ); building materials and insulation (Strachan ; Xing et al. ; Ordóñez and Modi ); building automation; and heating, ventilation, and air conditioning (HVAC) systems (Cho and Liu ; Guo et al. ; Sung et al ; Olivieri et al.…”
Section: Efficiency Approaches and Technologies For Space Heatingmentioning
confidence: 99%
“…; Runming and Short ); building materials and insulation (Strachan ; Xing et al. ; Ordóñez and Modi ); building automation; and heating, ventilation, and air conditioning (HVAC) systems (Cho and Liu ; Guo et al. ; Sung et al ; Olivieri et al.…”
Section: Efficiency Approaches and Technologies For Space Heatingmentioning
confidence: 99%
“…The measurements of the condenser load in the upper part of Figure 4 were obtained by using Equation (5) for the direct measurement, and using Equation (9) for the indirect measurement. The measurements of the compressor power in the mid of Figure 4 were obtained by using Equations (3) and (4) for the direct measurement, and using Equation (6) for the indirect measurement.…”
Section: Estimated Heat Pump Performance Based On Data Fusion Techniquementioning
confidence: 99%
“…Implementation of highly energy-efficient solutions and aiming to the zero energy or emission building will require even more building information and high instrumentation. Further, it was shown that by doing Continuous Commissioning, it was possible to achieve improvement in building operation and reduce energy costs [5]. To overcome these challenges, it is necessary to have a tool that can help to provide quality control on building energy performance, to perform fault detection and diagnosis, and overcome poor functional integration induced by information loss.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation